Polyphenols and Alkaloids in Byproducts of Longan Fruits (Dimocarpus Longan Lour.) and Their Bioactivities - Tang, Ya-Yuan; He, Xue-Mei; Sun, Jian; Li, Chang-Bao; Li, Li; Sheng, Jin-Feng; Xin, Ming; Li, Zhi-Chun; Zheng, Feng-Jin; Liu, Guo-Ming; Li, Jie-Min; Ling, Dong-Ning (Molecules (Basel, Switzerland), 2019)
The longan industry produces a large amount of byproducts such as pericarp and seed, resulting in environmental pollution and resource wastage. The present study was performed to systematically evaluate functional components, i.e., polyphenols (phenolics and flavonoids) and alkaloids, in longan byproducts and their bioactivities, including antioxidant activities, nitrite scavenging activities in simulated gastric fluid and anti-hyperglycemic activities in vitro. Total phenolic and total flavonoid contents in pericarp were slightly higher than those in seeds, but seeds possessed higher alkaloid content than pericarp. Four polyphenolic substances, i.e., gallic acid, ethyl gallate, corilagin and ellagic acid, were identified and quantified using high-performance liquid chromatography. Among these polyphenolic components, corilagin was the major one in both pericarp and seed. Alkaloid extract in seed showed the highest DPPH radical scavenging activity and oxygen radical absorbance capacity. Nitrite scavenging activities were improved with extract concentration and reaction time increasing. Flavonoids in seed and alkaloids in pericarp had potential to be developed as anti-hyperglycemic agents. The research result was a good reference for exploring longan byproducts into various valuable health-care products.